2023
DOI: 10.1159/000530082
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the Management of Home Parenteral Nutrition

Abstract: Introduction: Home parenteral nutrition (HPN) is a rare but challenging therapy and care for patients with mostly severe underlying diseases. We aimed to investigate patient-reported health-related quality of life (QOL) of patients receiving HPN and its development over time in particular. Methods: We assessed QOL of HPN patients in a prospective multicenter observational study (SWISSHPN II study). We designed a questionnaire to record symptoms and negative impacts of HPN and completed the validated Optum® SF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…questionnaire. The study showed that there was an improvement in physical health component summary scores (comparable with domain physical functioning QLQ-C30) when patients got PN [37]. Reasons for this difference could be that this study differs in intervention length, patient group (cancer and non-cancer patients, no palliative therapy) as well as the survey instrument.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…questionnaire. The study showed that there was an improvement in physical health component summary scores (comparable with domain physical functioning QLQ-C30) when patients got PN [37]. Reasons for this difference could be that this study differs in intervention length, patient group (cancer and non-cancer patients, no palliative therapy) as well as the survey instrument.…”
Section: Discussionmentioning
confidence: 87%
“…However, it remains understudied whether PN, while effectively increasing nutritional intake, has a negative impact on QoL in PaCa patients. A prospective observational study in participants with mixed conditions on the impact of PN on QoL showed a trend towards an improvement in the physical health component after three months, while the psychological component remained stable [37]. A systematic review of non-cancer patients criticized the lack of su cient literature on the impact of PN on QoL [38].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced QOL for patients correlates to fatigue, reduced oral intake, and the social burden of the time intensive treatment [ 12 ]. Since TPN relies heavily on the personal responsibility of the patient to administer and maintain sterility, it is of vital importance to recognize and address the social implications of the treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overnight infusions of HPN are widely recognized by patients and their clinicians to disrupt sleep [ 21 , 22 ]. Patients attribute sleep disruption to nocturnal polyuria, infusion pumps, intravenous lines, and ostomy output [ 23 ].…”
Section: Introductionmentioning
confidence: 99%